EFFECTIVENESS OF CHAKRA BALANCING ON PHYSICAL WELL BEING: A MULTIPLE CASE STUDY RESEARCH. (CAHIERS MAGELLANES-NS, 2024)
This paper is aimed at exploring the effectiveness of Chakra Balancing (Plexus Balancing) for improving physical well-being of an individual. 8 participants were purposefully selected and based on their physical ailments like diabetes, Blood Pressure etc. further, chakra balancing treatment plan has been made focusing their specific issues. This treatment plan includes pranayama, Chanting of specific beej mantra, mudras (Hand Gesture) guided meditation and specific affirmations. Then further their pre and post SUD (Subjective Unit of Distress) / Medical reports were compared. At the end all the participants have shown improvement in their physical well-being.